(untitled) (PerCursos, 2021)
In this article, a normative perspective is mentioned where urban resilience is established as the partial solution to the risk of disaster. It also proposes more attention to the supposed consequences of climate change, exposing worrying data on the rates of global changes in temperature, sea level rise, ice melting, etc., which are gradually increasing towards a path that will be lethal, both for nature and for the urban environment and people’s lives. Resilient urbanism is becoming increasingly relevant, besides trying to work the problem of risk exposure in the cities, the concept is related to measures to increase the capacity for prevention and adaptation of the territory or population, facing risks, disasters and unfavorable situations that a society supports or can support, and mainly, the transformation that this generates. However, the topic presents numerous challenges that must be analyzed and discussed for successful applications, even because most of the world’s population will eventually live in urbanized areas, so it is critical and very urgent to evaluate, planning, monitoring and applying urban resilience, especially in low-income countries, which are the most affected.